2021
DOI: 10.3390/jrfm14090439
|View full text |Cite
|
Sign up to set email alerts
|

Leader Dismissal or Continuity, President Longevity, Geographic Orientation of Owners and Team Performance: Insights from French Men’s Football, 1994–2016

Abstract: We investigated the impacts of president longevity and the geographic orientation of owners on team performance and on the effectiveness of dismissing the leader. In addition, we considered their impacts on the effectiveness of not dismissing the leader while the same organisation fires them at another time for a similar performance. We also tested the impact of dismissing the leader or not on performance. We explored the aforementioned risk-taking relationships in the first tier of French men’s football over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…An additional four studies considered the variation in the league table and the final league position, associating this sub-topic with the number of points won, the opponents’ strength or table position, the marks given by specialized newspapers to classify players’ individual performances, the context of the game (away or home game), and the total wage costs of the teams analysed [ 2 , 19 , 20 , 34 ]. Three studies included the physiological component [ 23 25 ], with one of these studies analysing the physiological effects for both training and competition [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An additional four studies considered the variation in the league table and the final league position, associating this sub-topic with the number of points won, the opponents’ strength or table position, the marks given by specialized newspapers to classify players’ individual performances, the context of the game (away or home game), and the total wage costs of the teams analysed [ 2 , 19 , 20 , 34 ]. Three studies included the physiological component [ 23 25 ], with one of these studies analysing the physiological effects for both training and competition [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the studies that focused on the points earned combined with variations and/or final league classification, some of the findings should be interpreted with caution. Scelles and Llorca [ 20 ], concluded that team performance improves after a HCs dismissal, however, maintaining the HC on the job could result in similar performance improvements. This evidence seems to support the idea of retaining the HC at the job, with gains related to sports performance and fewer costs associated with the non-dismissal of coaches and coaching stuff, in a mix of financial savings and promoting stability, time and space to develop the work of HC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations